Change management process in a mining company: Kotter’s 8-step change model - Laig, Roumel Bryan D.; Abocejo, Ferdinand T. (Journal of Management, Economics, and Industrial Organization, 2021)
This study assessed the change management process of a mining company following the 8-step change model advocated by Kotter in 1996. It investigated the association between change readiness factors which comprised job satisfaction, job uncertainty and organizational commitment and the change perception of the entire organization. The study employed a quantitative descriptive survey research design to methodically describe the observed change procedures, analyzed the association between change readiness factors and organizational change perception. Of the 192 mining company employees and stakeholders, 134 were randomly chosen through stratified sampling technique representing the operations division, support division and the organizational design group. Primary data were collected through survey questionnaires to stakeholders’ respondents holding various positions. The finding revealed that about 78 percent of the respondents agreed to step 8 of Kotter’s theory as instrumental in accomplishing the “make the change stick to the company’s culture”. They noted that the 8 steps from Kotter’s theory resulted to greater than 75 percent increase in productivity. There was a highly significant correlation (α < 0.01) between change readiness factors (job satisfaction, job uncertainty and organizational commitment) and the change perception of stakeholders. The higher the mining company adheres to change readiness factors, the more likely it can achieve success of change initiatives. In conclusion, the three identified change factors had direct bearing on the company stakeholders’ change perception. We recommend for a similar study to be pursued which could include other pertinent variables other than job satisfaction, job uncertainty and organizational commitment.